1976
DOI: 10.1083/jcb.69.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glucagon-producing cells (A cells) in dog gastric mucosa

Abstract: An immunocytochemical technique using specific antiglucagon serum reveals the presence of glucagon-containing cells situated exclusively in the oxyntic glandular mucosa of the dog stomach. Electron microscope examination of the mucosa demonstrated endocrine cells containing secretory granules with a round dense core surrounded by a clear halb, indistinguishable from secretory granules of pancreatic A cells. Like the alpha granules of pancreatic A cells, the granules of these gastric endocrine cells exhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The primary antisera used in this study were anti-porcine glucagon (donated by N. YANAIHARA, Shizuoka, GL-5, 1:1,000), anti-beefpork insulin (Immuno Nuclear Corp., Stillwater, Lot. 47291, 1:200), anti-human somatostatin (donated by S. ITO, Niigata, 1:500), anti-avian pancreatic polypeptide (donated by J. R. KIMMEL, Kansas City, Lance-10/5/81 Bleed, 1:1,000) and anti-porcine motilin (donated by N. YANAIHARA, R-1104, 1:500 (BAETENS et al, 1976) were computed to allow for sectioning artifacts. The degree of circularity (DC), an index of the shape of granules, was estimated from the perimeter (PM) and the area (A) of granules by the formula, DC=4rx (A-PM/2)/0.9PM2.…”
Section: Methodsmentioning
confidence: 99%
“…The primary antisera used in this study were anti-porcine glucagon (donated by N. YANAIHARA, Shizuoka, GL-5, 1:1,000), anti-beefpork insulin (Immuno Nuclear Corp., Stillwater, Lot. 47291, 1:200), anti-human somatostatin (donated by S. ITO, Niigata, 1:500), anti-avian pancreatic polypeptide (donated by J. R. KIMMEL, Kansas City, Lance-10/5/81 Bleed, 1:1,000) and anti-porcine motilin (donated by N. YANAIHARA, R-1104, 1:500 (BAETENS et al, 1976) were computed to allow for sectioning artifacts. The degree of circularity (DC), an index of the shape of granules, was estimated from the perimeter (PM) and the area (A) of granules by the formula, DC=4rx (A-PM/2)/0.9PM2.…”
Section: Methodsmentioning
confidence: 99%
“…Its primary structure is identical in most mammals including man, although some amino acid sequence changes are noted in glucagons from guinea pig or nonmammalian vertebrates (Irwin, 2001). Glucagon is synthesized mainly in the A-cells present at the periphery of the islets of Langerhans (Baum et al, 1962) and is also detected in specific cells in the stomach and intestine in some species (Baetens et al, 1976), as well as in specialized neurons of the central nervous system. Isolation of cDNAs encoding glucagon (Lund et al, 1982;Lopez et al, 1983) showed that the peptide is produced from a 160-amino acid precursor, proglucagon, which also contains two additional glucagon-like sequences at its carboxyl terminus (GLP-1 and GLP-2), which were subsequently shown to display specific biological activities (Drucker, 1998).…”
Section: The Glucagon Receptormentioning
confidence: 99%
“…Glucagon is synthesized mainly in the α-cells at the periphery of the islets of Langerhan's (Baum et al, 1962). Glucagon can be detected in specific cells in the stomach and intestine in some species (Baetens et al, 1976), as well as in specialized neurons of the CNS. Isolation of cDNAs encoding glucagon (Lund et al, 1982) showed that the peptide is produced from a 160-amino acid precursor, proglucagon, which also contains two additional glucagon-like sequences at its carboxyl terminus, GLP-1 and GLP-2, which were subsequently shown to display specific biological activities (Drucker, 1998).…”
Section: Glucagon and Glucagon-like Peptides (Glps)mentioning
confidence: 99%